IMPLEMENTASI PEMASARAN DIGITAL DAN APLIKASI AKUNTANSI DI PUSAT INFORMASI KONSELING REMAJA BANJARSARI - Dian Nur Mastuti; Yuniatin T.D.K.W; Basuki Sri Rahayu; Jarot Santosa (Mafaza : Jurnal Pengabdian Masyarakat, 2023)
Indonesia is entering the Demographic Bonus period which refers to a phenomenon of increasing the number of productive age population (15-64 years) which brings benefits to the economy of a region, meaning that youth play an important role in advancing the country's economy. Optimizing the potential of youth as a supporter of the progress of the country's economy needs to be accompanied and given training so that it is directed and can maximize the skills of youth. This training and assistance is carried out through Community Service activities using smartphones and social media as media for generating rupiah. Community Service activities were carried out with 40 teenagers at the Banjarsari Youth Counseling Information Center in several stages starting from initial mapping, digital marketing training through imooji and canva, as well as accounting application training through the Financial Records Application which can be downloaded from the playstore. The activity continued with mentoring and a question and answer session. The success of Community Service activities is measured by the ability of participants to take part in training and mentoring on digital marketing and accounting applications via smartphones. Survey after activities showing result that 75% of the participants were able to take part in the activities well. The survey was conducted in several aspects and found that 79% of participants felt that the training activities were very useful, 75% of participants felt that the training provided was easy to follow and apply, and 80% of participants were satisfied with the community service activities they participated in. This activity is beneficial for youth as a whole as additional skills in the technological era and has the potential to be further developed through further community service activities.